Isthmin-1 and spexin as promising novel biomarker candidates for invasive ductal breast carcinoma - Turk, Ahmet; Metin, Tuba Ozcan; Kuloglu, Tuncay; Yilmaz, Mustafa; Artas, Gokhan; Ozercan, I. Hanifi; Hancer, Serhat (Churchill Livingstone, 2024)
Introduction: Breast cancer is one of the most common malignant tumors and a leading cause of cancer-related death in women. Research is focusing on biomarkers linked to breast cancer, particularly two novel proteins: isthmin-1 (ISM-1) and spexin (SPX), which require further investigation. Material and methods: The study involved 20 healthy controls and 60 patients with invasive ductal carcinoma, categorized into three groups: Grade I (n=20), Grade II (n=20), and Grade III (n=20). Levels of ISM-1 and SPX in tissue were analyzed using immunohistochemistry alongside the clinicopathologic data of patients. Results: There were no statistically significant differences in age, menopausal status, ER, PR, and Cerb-B2 values across grades (p>0.05). Tumor diameters showed a significant increase in Grade I compared to Grade II (p<0.05), while no significant difference was noted between Grade II and Grade III, although diameters were larger in Grade III compared to Grade I (p<0.05). Notably, ISM-1 immunoreactivity decreased, and SPX immunoreactivity increased significantly across all grades compared to normal tissue (p<0.05), with no significant differences between tumor grades for these markers (p>0.05). Conclusions: This study presents new findings on ISM-1 and SPX expression in invasive ductal breast carcinoma. The decrease in ISM-1 and increase in SPX suggest a need for further research into the relationship between adipokines and tumor development in breast cancer.
Keywords: Breast cancer; Invasive ductal carcinoma; Isthmin-1; Spexin